Comparison of cpe Values from CFD and Wind Tunnel Testing for Various Surface Roughnesses - Cruz Samuel; Palko Milan (Slovak Journal of Civil Engineering, 2025)
This paper presents a comparative analysis of the pressure coefficient (cpe) values obtained through wind tunnel experiments and CFD simulations using two approaches for modeling surface roughness i.e, geometrically explicit roughness and equivalent roughness constants in ANSYS Fluent. Five levels of surface roughness were analyzed to assess whether simplified roughness constants can sufficiently approximate geometrically modeled surfaces. The results show close agreement for most cases, which indicates the potential for computational simplification.